Teaching practice and autonomous learning in students of Bilingual Intercultural Pedagogical Higher Education - Alcarraz Carbajal, Bibiano (2023)
This descriptive research has the purpose of knowing the relationship between teaching practice and autonomous learning in students of higher pedagogical education. For this reason, a basic investigation with a correlational investigation design was carried out, with a population of 64 students, from which a sample of 26 students was selected through the non-probabilistic sampling technique, in the data collection the survey technique was used. through the questionnaire. In the hypothesis test, the Kendall Tau b statistician was used, among the main findings they show a value equal to 0.4, which shows the presence of a moderate relationship between teaching practice and autonomous learning, 0.468 determines the presence of a moderate relationship. relationship between teaching practice and academic habits, 0.248 indicates the presence of a low relationship between teaching practice and cognitive skills, 0.292 shows a low relationship between teaching practice and the ability to adapt in bilingual intercultural pedagogical higher education students. The results show that there is a moderate relationship between teaching practice, with autonomous learning and academic habits; but there is no significant relationship between teaching practice, with cognitive habits and adaptability in students.